2017
DOI: 10.1002/lt.24754
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant modulates gut microbial dysbiosis and cognitive function in cirrhosis

Abstract: Liver transplantation (LT) improves daily function and cognition in patients with cirrhosis, but a subset of patients can remain impaired. Unfavorable microbiota or dysbiosis is observed in patients with cirrhosis, but the effect of LT on microbial composition, especially with poor post-LT cognition, is unclear. The aims were to determine the effect of LT on gut microbiota and to determine whether gut microbiota are associated with cognitive dysfunction after LT. We enrolled outpatient patients with cirrhosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 29 publications
3
95
2
Order By: Relevance
“…In a later case–control study, the same authors found that cognitive performance of elderly patients was negatively correlated with the relative abundance of Enterobacteriaceae and Porphyromonadaceae and positively correlated with the Lactobacillales relative abundance, irrespective of the presence of cirrhosis 56. Finally, liver transplantation proved to be able to reduce gut microbiota dysbiosis associated with advanced cirrhosis, with a simultaneous improvement in cognitive symptoms 57. The presence of a gut–brain axis modulating cognitive function in gastrointestinal and liver diseases is also supported by the observation that rifaximin administration is associated with cognition improvement in cirrhosis,58 and that irritable bowel syndrome, a functional disorder implying mild gut microbiota dysbiosis, is associated with an increased risk of dementia 59…”
Section: Resultsmentioning
confidence: 91%
“…In a later case–control study, the same authors found that cognitive performance of elderly patients was negatively correlated with the relative abundance of Enterobacteriaceae and Porphyromonadaceae and positively correlated with the Lactobacillales relative abundance, irrespective of the presence of cirrhosis 56. Finally, liver transplantation proved to be able to reduce gut microbiota dysbiosis associated with advanced cirrhosis, with a simultaneous improvement in cognitive symptoms 57. The presence of a gut–brain axis modulating cognitive function in gastrointestinal and liver diseases is also supported by the observation that rifaximin administration is associated with cognition improvement in cirrhosis,58 and that irritable bowel syndrome, a functional disorder implying mild gut microbiota dysbiosis, is associated with an increased risk of dementia 59…”
Section: Resultsmentioning
confidence: 91%
“…The liver transplant is not a perfect model, because posttransplant patients are on antiviral, antibiotic, and immunosuppressive therapies; however, these patients still provide useful information on the impact that replacement of a diseased liver with a healthy liver has on the microbiota. Longitudinal evaluation of patients with liver transplant showed a significant improvement in gut microbiota diversity over time, but the restoration of microbial diversity did not reach the levels observed in age-matched healthy controls (59). Interestingly, changes in Proteobacteria and Firmicutes were related to the level of cognitive improvement after transplant.…”
Section: Gut Dysbiosismentioning
confidence: 87%
“…The intestine-derived endotoxin is known to be involved in the development of liver diseases, such as liver fibrosis [12] and alcoholic liver disease [13]. It has been suggested that gut microbe is strongly associated with induction of intestinal damage while extensive analysis of pathological changes in the intestine during the development of liver injury or fibrosis has not been studied well.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the oral administration of S. boulardii improved the liver function in CCl 4 -treated rats, and the preventive treatment of this probiotic yeast suppressed the progression of liver fibrosis [7]. Liver transplant has also been reported to improve the composition of the gut microbiome and cognitive impairment in cirrhotic patients [12]. Increased translocation of bacteria and bacterial products from the intestine may impair liver homeostasis and enhance liver inflammation through activation of the innate immune system [11, 29].…”
Section: Discussionmentioning
confidence: 99%